2007
DOI: 10.1017/s0014479707005303
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Yield Sustainability and Financial Returns From Grain Legume–maize Intercrops on a Sandy Soil in Subhumid North Central Zimbabwe

Abstract: To measure the yield and financial returns from five grain legume-maize intercrop combinations over 12 years of cropping, a field experiment was conducted on a loamy sand soil in the subhumid unimodal rainfall environment of Domboshava in north-central Zimbabwe. Inputs and management followed smallholder practice, including partial grazing of crop residues and a zero mineral fertilizer treatment. The intercropped legumes grew moderately well most years. Cowpea averaged the highest grain yield (0.244 t ha −1 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 11 publications
(12 reference statements)
7
35
1
1
Order By: Relevance
“…Ngwira et al (2012b) reported similar results from Malawi in maize-legume intercropping systems with minimum tillage as well as Rusinamhodzi et al (2012) in central Mozambique. Our results support earlier findings of Sakala (1994) who reported a yield penalty of only 10% when intercropping with pigeonpea, although yield penalties can also be much larger especially when the timing between main crop and intercrop is not well synchronized (Shumba et al, 1990;Waddington et al, 2007).…”
Section: Yield Benefits Of Conservation Agriculture Over Conventionalsupporting
confidence: 92%
“…Ngwira et al (2012b) reported similar results from Malawi in maize-legume intercropping systems with minimum tillage as well as Rusinamhodzi et al (2012) in central Mozambique. Our results support earlier findings of Sakala (1994) who reported a yield penalty of only 10% when intercropping with pigeonpea, although yield penalties can also be much larger especially when the timing between main crop and intercrop is not well synchronized (Shumba et al, 1990;Waddington et al, 2007).…”
Section: Yield Benefits Of Conservation Agriculture Over Conventionalsupporting
confidence: 92%
“…These include improved soil and water conservation methods (e.g., Fowler and Rockström 2001;Hobbs et al 2008;Erenstein et al 2012), integrated nutrient management (e.g., Vanlauwe et al 2010;Timsina et al 2010Timsina et al , 2011, the retention and use of biodiversity on crop fields (Mapfumo et al 2005;Snapp et al 2010) and the improved management of farm fields with different nutrient status (e.g., Giller et al 2006;Tittonell et al 2008). Across Sub-Saharan Africa, many of the more-traditional maize systems maintain productivity while reducing abiotic and biotic environmental impacts by intercropping or rotating leguminous trees and shrubs, and annual legumes with maize (Snapp et al 1998(Snapp et al , 2010Waddington et al 2007;Ajayi et al 2011;Pretty et al 2011), or by incorporating legume weed residues into croplands (Mapfumo et al 2005). The expansion of such practices should be encouraged.…”
Section: Good Practices To Manage Crop X Environment Interactionsmentioning
confidence: 99%
“…Intercropping maize and legumes is another way to achieve food security and cash income for smallholder farmers, and abundant literature from Southern Africa supports this observation 81,102,[130][131][132][133] . Although intercropping with legumes is associated with many benefits, including improving soil structure and fertility and the potential to increase farm income through selling legume grain, the potential of legumes within farming systems of Southern Africa is currently limited by a plethora of constraints.…”
Section: Intensificationmentioning
confidence: 99%